(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The paper examined the factors affecting the Creativity and Academic Performance of Primary School Pupils in Nigeria. Primary education is the foundation on which further education is built and has two main purposes. The first purpose is to produce a literate and numerate population that can jointly deal with problems both at home and at work. Therefore, the paper recommended that Parents and teachers should find ways of promoting the level of creativity of the pupils, as a high level of creativity has an influence on academic performance. Also, Parents of pupils with low levels of creativity should give their children more support and encouragement to improve their level of academic performance in their learning subjects